Penile Rehabilitation and Treatment Options for Erectile Dysfunction Following Radical Prostatectomy and Radiotherapy: A Systematic Review - Nicolai, Melianthe; Urkmez, Ahmet; Sarikaya, Selcuk; Fode, Mikkel; Falcone, Marco; Albersen, Maarten; Gul, Murat; Hatzichristodoulou, Georgios; Capogrosso, Paolo; Russo, Giorgio Ivan (Frontiers in Surgery, 2021)
After radical prostatectomy (RP) or radiotherapy (RT) for prostate cancer, erectile dysfunction (ED) is the main complication next to urinary incontinence, affecting quality of life. The pathophysiology of ED after these treatments is believed to include neuropraxia causing reduced oxygenation and structural changes of the tissue in the corpora cavernosa. Next to the option of sparing the nerves during RP, research has been focusing on methods for penile rehabilitation after RP and RT, since it occurs often, even after nerve-sparing techniques were used. In animal studies, the use of phosphodiesterase type 5 inhibitors (PDE5i) after cavernous nerve damage is supported, but results in human studies are contradictory. Non-medical treatment options such as vacuum device therapy, hyperbaric oxygen therapy, yoga, aerobic, or pelvic floor training may be helpful, but evidence is scarce. Clear guidelines for penile rehabilitation are not yet available. However, care and support for ED after RP and RT is highly demanded by a large group of patients, so measures have to be taken even though the evidence is not strong yet. In this systematic review, an overview of the literature for penile rehabilitation and treatment options for ED after RP and RT is provided, using only randomized controlled trials (RCT).